Propriedades físicas e térmicas de grãos de quinoa (Chenopodium quinoa Willd) em função do teor de água - (:unkn) unknown (Universidade Estadual de Goiás, 2009)
This study aimed to determine and shape the physical, thermal and aerodynamic grain quinoa at different water contents. Beans were used quinoa, BRS Piabiru, harvested during winter 2008, the farm Don Bosco Planaltina - DF. The physical properties were investigated in seven water contents (12.8, 13.8, 14.8, 15.7, 17.6, 18.3 and 19.7% db), among them, roundness, sphericity , the equivalent diameter, porosity, thousand grain weight and true density and apparent, were determined from measurements of orthogonal axes and weighing the masses. The thermal properties were determined at five moisture contents (10.1, 11.7, 13.5, 16.0, 17.6% db). The thermal conductivity and thermal diffusivity were determined using the infinite cylinder fitted with a linear central heat source. The specific heat was determined by indirect method based on the mass density and the other thermal properties. The aerodynamic properties, terminal velocity and drag coefficient of drag of the grains of quinoa were determined in seven levels of water, using a device composed of a centrifugal fan connected to a tube of acrylic. The properties of the grains of quinoa, BRS Piabiru, were evaluated in a randomized design in which treatments were water content. In choosing the best model were considered: the significance of regression coefficients by t test, the magnitude of the coefficient of determination (R ²) and relative error (P). The results showed that the roundness and sphericity are invariant with increasing water content. The bulk density decreases with increasing water content. The true density, porosity and thousand grain weight increased with increasing water content. The thermal conductivity of the grains of quinoa increased from 0.1878 to 0.2293 W m-1 C-1, the specific heat increased from 2.8 to 3.4 J kg-1 C-1, the diffusivity decreased from 0, 00010018 0.00010013 to m2 s-1, for all water contents between 10.1 and 17.6% db For water contents between 12.8 and 19.7% db, the experimental and theoretical terminal velocity increased from 2.92 to 3.35 m s-1 and 1.32 to 1.44 ms-1 for aerodynamic coefficients of experimental and theoretical drag from 0.09 to 0.10 and 0.156 to 0.158, respectively, with increasing water content of 12.8 to 19.7% db.
Keywords: Armazenamento de grãos; Forma e tamanho dos grãos; Condutividade térmica; Velocidade terminal; Grains storage; Size and form of grains; Thermal conductivity; Terminal velocity; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA DE PROCESSAMENTO DE PRODUTOS AGRICOLAS::ARMAZENAMENTO DE PRODUTOS AGRICOLAS